2009
DOI: 10.1186/1756-3305-2-39
|View full text |Cite
|
Sign up to set email alerts
|

Community-directed delivery of doxycycline for the treatment of onchocerciasis in areas of co-endemicity with loiasis in Cameroon

Abstract: Background: Severe side effects following ivermectin treatment of onchocerciasis in areas of coendemicity with loaisis have been an impediment for the work of the African Programme for Onchocerciasis Control (APOC) in forested regions of several countries. Doxycycline has been shown to be effective in the treatment of onchocerciasis and has the added advantages of killing adult Onchocerca volvulus but neither adult Loa loa nor their microfilariae. This drug therefore offers great potential for the treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
78
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 34 publications
3
78
0
Order By: Relevance
“…However, significant adulticidal activity (killing of 60 to 70% of female worms) required a regimen of 200 mg/day for 6 weeks (20). This relatively protracted course of treatment, coupled with contraindications in children below 8 years of age and in pregnant or lactating women, have prevented approval of DOX for MDA to date; this is despite the very high rates of compliance evident in a clinical trial that was conducted in a region of Cameroon where loiasis is endemic (22). Nevertheless, DOX has been applied in a small onchocerciasis focus in Venezuela to expedite elimination efforts (23).…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…However, significant adulticidal activity (killing of 60 to 70% of female worms) required a regimen of 200 mg/day for 6 weeks (20). This relatively protracted course of treatment, coupled with contraindications in children below 8 years of age and in pregnant or lactating women, have prevented approval of DOX for MDA to date; this is despite the very high rates of compliance evident in a clinical trial that was conducted in a region of Cameroon where loiasis is endemic (22). Nevertheless, DOX has been applied in a small onchocerciasis focus in Venezuela to expedite elimination efforts (23).…”
mentioning
confidence: 66%
“…Although DOX is clearly more efficacious than ivermectin, the latter can suppress Mf densities (and thus, disease manifestations) for up to 1 year following a single dose of 150 g/kg, which makes it highly amenable to MDA programs (4). In a clinical trial in a area of Cameroon where loiasis is endemic, community-wide distribution of daily DOX therapy for 6 weeks was accompanied by very high rates of compliance (22), but to date, this has not resulted in wider application of DOX by APOC.…”
Section: Discussionmentioning
confidence: 99%
“…Diethylcarbamazine is also contra-indicated because of the risk of a strong Mazzotti reaction and exacerbation of ocular pathology, but a combination of doxycycline and albendazole [83] or doxycycline alone [84] can be used under these circumstances. Apart from ivermectin, other microfilaricides include moxidectin, which has a longer-lasting effect than ivermectin and with little re-population [85] but it has yet to be licensed.…”
Section: Microfilaricidesmentioning
confidence: 99%
“…Wanji and colleagues, however, proved the skeptics wrong when they showed that more than 97% of ϳ13,000 people from villages where the infection is endemic who started doxycycline completed a 6-week regimen after community-directed explanation and organization of the delivery (community-directed treatment) (84). Current follow-up studies are aimed at assessing the impact of community-directed doxycycline administration (which comprised, on average, about 74% of the eligible population having started the treatment) on community microfilarial load and thus its impact on transmission.…”
mentioning
confidence: 99%